Bessel Functions - 10.35 Generating Function and Associated Series

From testwiki
Revision as of 16:58, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
10.35.E1 e 1 2 z ( t + t - 1 ) = m = - t m I m ( z ) superscript 𝑒 1 2 𝑧 𝑡 superscript 𝑡 1 superscript subscript 𝑚 superscript 𝑡 𝑚 modified-Bessel-first-kind 𝑚 𝑧 {\displaystyle{\displaystyle e^{\frac{1}{2}z(t+t^{-1})}=\sum_{m=-\infty}^{% \infty}t^{m}I_{m}\left(z\right)}}
e^{\frac{1}{2}z(t+t^{-1})} = \sum_{m=-\infty}^{\infty}t^{m}\modBesselI{m}@{z}
( m + k + 1 ) > 0 𝑚 𝑘 1 0 {\displaystyle{\displaystyle\Re(m+k+1)>0}}
exp((1)/(2)*z*(t + (t)^(- 1))) = sum((t)^(m)* BesselI(m, z), m = - infinity..infinity)
Exp[Divide[1,2]*z*(t + (t)^(- 1))] == Sum[(t)^(m)* BesselI[m, z], {m, - Infinity, Infinity}, GenerateConditions->None]
Failure Aborted Skipped - Because timed out Skipped - Because timed out
10.35.E2 e z cos θ = I 0 ( z ) + 2 k = 1 I k ( z ) cos ( k θ ) superscript 𝑒 𝑧 𝜃 modified-Bessel-first-kind 0 𝑧 2 superscript subscript 𝑘 1 modified-Bessel-first-kind 𝑘 𝑧 𝑘 𝜃 {\displaystyle{\displaystyle e^{z\cos\theta}=I_{0}\left(z\right)+2\sum_{k=1}^{% \infty}I_{k}\left(z\right)\cos\left(k\theta\right)}}
e^{z\cos@@{\theta}} = \modBesselI{0}@{z}+2\sum_{k=1}^{\infty}\modBesselI{k}@{z}\cos@{k\theta}
( 0 + k + 1 ) > 0 , ( k + k + 1 ) > 0 formulae-sequence 0 𝑘 1 0 𝑘 𝑘 1 0 {\displaystyle{\displaystyle\Re(0+k+1)>0,\Re(k+k+1)>0}}
exp(z*cos(theta)) = BesselI(0, z)+ 2*sum(BesselI(k, z)*cos(k*theta), k = 1..infinity)
Exp[z*Cos[\[Theta]]] == BesselI[0, z]+ 2*Sum[BesselI[k, z]*Cos[k*\[Theta]], {k, 1, Infinity}, GenerateConditions->None]
Failure Successful Skipped - Because timed out Successful [Tested: 70]
10.35.E3 e z sin θ = I 0 ( z ) + 2 k = 0 ( - 1 ) k I 2 k + 1 ( z ) sin ( ( 2 k + 1 ) θ ) + 2 k = 1 ( - 1 ) k I 2 k ( z ) cos ( 2 k θ ) superscript 𝑒 𝑧 𝜃 modified-Bessel-first-kind 0 𝑧 2 superscript subscript 𝑘 0 superscript 1 𝑘 modified-Bessel-first-kind 2 𝑘 1 𝑧 2 𝑘 1 𝜃 2 superscript subscript 𝑘 1 superscript 1 𝑘 modified-Bessel-first-kind 2 𝑘 𝑧 2 𝑘 𝜃 {\displaystyle{\displaystyle e^{z\sin\theta}=I_{0}\left(z\right)+2\sum_{k=0}^{% \infty}(-1)^{k}I_{2k+1}\left(z\right)\sin\left((2k+1)\theta\right)+2\sum_{k=1}% ^{\infty}(-1)^{k}I_{2k}\left(z\right)\cos\left(2k\theta\right)}}
e^{z\sin@@{\theta}} = \modBesselI{0}@{z}+2\sum_{k=0}^{\infty}(-1)^{k}\modBesselI{2k+1}@{z}\sin@{(2k+1)\theta}+2\sum_{k=1}^{\infty}(-1)^{k}\modBesselI{2k}@{z}\cos@{2k\theta}
( 0 + k + 1 ) > 0 , ( ( 2 k + 1 ) + k + 1 ) > 0 , ( ( 2 k ) + k + 1 ) > 0 formulae-sequence 0 𝑘 1 0 formulae-sequence 2 𝑘 1 𝑘 1 0 2 𝑘 𝑘 1 0 {\displaystyle{\displaystyle\Re(0+k+1)>0,\Re((2k+1)+k+1)>0,\Re((2k)+k+1)>0}}
exp(z*sin(theta)) = BesselI(0, z)+ 2*sum((- 1)^(k)* BesselI(2*k + 1, z)*sin((2*k + 1)*theta), k = 0..infinity)+ 2*sum((- 1)^(k)* BesselI(2*k, z)*cos(2*k*theta), k = 1..infinity)
Exp[z*Sin[\[Theta]]] == BesselI[0, z]+ 2*Sum[(- 1)^(k)* BesselI[2*k + 1, z]*Sin[(2*k + 1)*\[Theta]], {k, 0, Infinity}, GenerateConditions->None]+ 2*Sum[(- 1)^(k)* BesselI[2*k, z]*Cos[2*k*\[Theta]], {k, 1, Infinity}, GenerateConditions->None]
Aborted Failure Manual Skip! Skipped - Because timed out
10.35.E4 1 = I 0 ( z ) - 2 I 2 ( z ) + 2 I 4 ( z ) - 2 I 6 ( z ) + 1 modified-Bessel-first-kind 0 𝑧 2 modified-Bessel-first-kind 2 𝑧 2 modified-Bessel-first-kind 4 𝑧 2 modified-Bessel-first-kind 6 𝑧 {\displaystyle{\displaystyle 1=I_{0}\left(z\right)-2I_{2}\left(z\right)+2I_{4}% \left(z\right)-2I_{6}\left(z\right)+\cdots}}
1 = \modBesselI{0}@{z}-2\modBesselI{2}@{z}+2\modBesselI{4}@{z}-2\modBesselI{6}@{z}+\dotsb
( 0 + k + 1 ) > 0 , ( 2 + k + 1 ) > 0 , ( 4 + k + 1 ) > 0 , ( 6 + k + 1 ) > 0 formulae-sequence 0 𝑘 1 0 formulae-sequence 2 𝑘 1 0 formulae-sequence 4 𝑘 1 0 6 𝑘 1 0 {\displaystyle{\displaystyle\Re(0+k+1)>0,\Re(2+k+1)>0,\Re(4+k+1)>0,\Re(6+k+1)>% 0}}
1 = BesselI(0, z)- 2*BesselI(2, z)+ 2*BesselI(4, z)- 2*BesselI(6, z)+ ..
1 == BesselI[0, z]- 2*BesselI[2, z]+ 2*BesselI[4, z]- 2*BesselI[6, z]+ \[Ellipsis]
Error Failure -
Failed [7 / 7]
Result: Plus[Complex[-9.440290591519046*^-8, -1.7199789187696823*^-7], Times[-1.0, ]]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}

Result: Plus[Complex[-9.924736610669727*^-8, -1.6360842739013975*^-7], Times[-1.0, ]]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

... skip entries to safe data
10.35.E5 e + z = I 0 ( z ) + 2 I 1 ( z ) + 2 I 2 ( z ) + 2 I 3 ( z ) + superscript 𝑒 𝑧 modified-Bessel-first-kind 0 𝑧 2 modified-Bessel-first-kind 1 𝑧 2 modified-Bessel-first-kind 2 𝑧 2 modified-Bessel-first-kind 3 𝑧 {\displaystyle{\displaystyle e^{+z}=I_{0}\left(z\right)+2I_{1}\left(z\right)+2% I_{2}\left(z\right)+2I_{3}\left(z\right)+\cdots}}
e^{+ z} = \modBesselI{0}@{z}+ 2\modBesselI{1}@{z}+2\modBesselI{2}@{z}+ 2\modBesselI{3}@{z}+\dotsb
( 0 + k + 1 ) > 0 , ( 1 + k + 1 ) > 0 , ( 2 + k + 1 ) > 0 , ( 3 + k + 1 ) > 0 formulae-sequence 0 𝑘 1 0 formulae-sequence 1 𝑘 1 0 formulae-sequence 2 𝑘 1 0 3 𝑘 1 0 {\displaystyle{\displaystyle\Re(0+k+1)>0,\Re(1+k+1)>0,\Re(2+k+1)>0,\Re(3+k+1)>% 0}}
exp(+ z) = BesselI(0, z)+ 2*BesselI(1, z)+ 2*BesselI(2, z)+ 2*BesselI(3, z)+ ..
Exp[+ z] == BesselI[0, z]+ 2*BesselI[1, z]+ 2*BesselI[2, z]+ 2*BesselI[3, z]+ \[Ellipsis]
Error Failure -
Failed [7 / 7]
Result: Plus[Complex[-0.003384051289485407, 0.00475177611436145], Times[-1.0, ]]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}

Result: Plus[Complex[-0.002576303532707505, 0.004074841322498801], Times[-1.0, ]]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

... skip entries to safe data
10.35.E5 e - z = I 0 ( z ) - 2 I 1 ( z ) + 2 I 2 ( z ) - 2 I 3 ( z ) + superscript 𝑒 𝑧 modified-Bessel-first-kind 0 𝑧 2 modified-Bessel-first-kind 1 𝑧 2 modified-Bessel-first-kind 2 𝑧 2 modified-Bessel-first-kind 3 𝑧 {\displaystyle{\displaystyle e^{-z}=I_{0}\left(z\right)-2I_{1}\left(z\right)+2% I_{2}\left(z\right)-2I_{3}\left(z\right)+\cdots}}
e^{- z} = \modBesselI{0}@{z}- 2\modBesselI{1}@{z}+2\modBesselI{2}@{z}- 2\modBesselI{3}@{z}+\dotsb
( 0 + k + 1 ) > 0 , ( 1 + k + 1 ) > 0 , ( 2 + k + 1 ) > 0 , ( 3 + k + 1 ) > 0 formulae-sequence 0 𝑘 1 0 formulae-sequence 1 𝑘 1 0 formulae-sequence 2 𝑘 1 0 3 𝑘 1 0 {\displaystyle{\displaystyle\Re(0+k+1)>0,\Re(1+k+1)>0,\Re(2+k+1)>0,\Re(3+k+1)>% 0}}
exp(- z) = BesselI(0, z)- 2*BesselI(1, z)+ 2*BesselI(2, z)- 2*BesselI(3, z)+ ..
Exp[- z] == BesselI[0, z]- 2*BesselI[1, z]+ 2*BesselI[2, z]- 2*BesselI[3, z]+ \[Ellipsis]
Error Failure -
Failed [7 / 7]
Result: Plus[Complex[-0.0024389937896763803, 0.0042567403420422645], Times[-1.0, ]]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}

Result: Plus[Complex[-0.0020316532349716754, 0.004934003265463338], Times[-1.0, ]]
Test Values: {Rule[z, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

... skip entries to safe data